Konsep Tabannī dalam Tafsir An-Nur: Analisis Pemikiran Hasbi Ash-Shiddieqy - Aulia Rahmaini; Ahmad Zuhri; Nur Aisah Simamora (Kamaya: Jurnal Ilmu Agama, 2025)
The phenomenon of child adoption (tabannī), from the pre-Islamic era to the modern period, has raised significant issues concerning lineage, inheritance, and guardianship. The Qur’an, particularly in QS. al-Ahzab verses 4–5, 37, and 40, abolished the Jahiliyyah practice of tabannī and emphasized the importance of preserving genealogical clarity. In the Indonesian context, adoption is still frequently equated with biological children, revealing a gap between the ideal principles of Islamic law and prevailing social practices. This study aims to examine Hasbi Ash-Shiddieqy’s thought on adoption as articulated in Tafsir An-Nur and to evaluate its relevance to contemporary Indonesian legal frameworks. The research employs a qualitative library-based method, with Tafsir An-Nur as the primary source, supported by classical and modern exegeses, Islamic jurisprudence, scholarly articles, and family law regulations. Data were analyzed through a thematic (maudhu‘i) approach combined with descriptive-analytical methods to explore Hasbi’s interpretation regarding the implications of adoption for lineage, inheritance, and guardianship. The findings reveal that Hasbi rejected the legal assimilation of adopted children with biological children but strongly emphasized the importance of kafālah (care and guardianship), which ensures love, education, and social protection without erasing the child’s biological lineage. Regarding inheritance, adopted children do not have the right to receive a share as heirs, yet provision is possible through the mechanism of obligatory bequest (wasiat wajibah), in line with the Compilation of Islamic Law (KHI) in Indonesia. Hasbi’s perspective demonstrates a distinctly Nusantara exegetical style that is moderate, contextual, and socially responsive. Consequently, this study contributes theoretically by enriching Nusantara Qur’anic exegesis studies and practically by providing normative foundations for formulating adoption policies in modern Indonesia that balance Islamic legal principles with the protection of adopted children’s rights.